PENINGKATAN KETAHANAN KELUARGA MELALUI OPTIMALISASI PERAN JAMAAH MUSLIMAH DI MASJID RAYA AL-MUHAJIRIN KABUPATEN BEKASI - Fahrany, Sofia; Yasin, Rahman; Sirojuddin, Sirojuddin (Spektra: Jurnal Ilmu-ilmu Sosial, 2024)
In recent years, Indonesia has experienced a decline in morals, akhlakul madzmumah (despicable morals), a decline in the quality of good behavior due to lack of parental supervision and the influence of gadgets, online media that can be accessed, with any livelihood in the palm of your hand. The rise in cases of delinquency and crime such as cases of drug abuse, and sexual deviations among lesbians, gays, bisexuals and transgender people, where sexually transmitted diseases are transmitted. According to data from the National Narcotics Agency, as many as 2.2 million Indonesian teenagers are drug abusers, according to Imelda to Radio Republik Indonesia on Wednesday, June 26 2024. . Indonesia has a population of 3% LGBT. In other words, of the 250 million Indonesian population, around 7.5 million of whom are LGBT due to parental negligence in educating their children, meaning that out of 100 people gathered, 3 of them are LGBT (CIA research reported by sixpackmagazinedotnet, research by Hasnah journal of the Nursing Study Program, FKIK UIN Alaudi Makasar). Family in Arabic is called ahlun from ahal which means marriage, apart from the word ahlun the words which mean family are, asyirah (family of descendants), and qurba (those related to kinship). Home and family are the main basis for religious education from an early age which is usually carried out by the mother (Al-Ummu Madrasatul “Ula). As Rasulullah SAW said, "Sun your homes with prayer and reading the Koran."Strengthening family resilience can be a way to produce the next generation who are strong, like religious injunctions, so they can survive in overcoming life's problems. As Allah SWT says in Surah An-nisa verse 9 "And fear Allah, those who leave behind them weak children, whose welfare they fear. Therefore, let them fear Allah, and let them speak the right words."Family resilience through optimizing the role of the Muslim congregation plays an important role in the nation's resilience. A quality family will give birth to a quality next generation of the nation (qurrata a'yun). In this research we used qualitative descriptive methods, journals and e-journals, scientific books and e-books, because they are systematic, in collecting data through data triangulation, validation, observation and interviews. It is hoped that the results of this research will give birth to the nation's next generation towards baldatun thayyibatun wa rabbun ghafur. Amen, Ya Rabbal'alamin.